(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Harishankar Jaladas is one of the most powerful and popular Bangladeshi novelists and short story writers in present time. He has represented the life of marginalized people in most of his works. Being a representative of ‘Kaibartya’ Community he got the chance to closely observe the life and culture, struggle and crisis of the people of that society. In the novel ‘Jalaputra’, Harishankar has introduced the lifestyle, struggle and crisis of the ‘Kaibartya’ community those who have been neglected by the upper castes for ages. The Dalit people have an important place in this novel. Novelist’s socio-political and cultural ideas, beliefs as well as his profound love for his own community are vividly presented in this novel. The present paper tries to show fishermen’s life in different aspects in the context of the novel ‘Jalaputra’